IMPLEMENTATION OF IDLE ASSET GOVERNANCE POLICY AND ITS IMPLICATIONS ON REGIONAL ASSET OPTIMIZATION IN BANYUWANGI REGENCY - Qurya Adjeng Pitaloca; Hary Priyanto; Erna Agustina (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Idle asset management is a crucial issue in regional governance because it impacts the optimization of development resources. In Banyuwangi Regency, despite the availability of a regulatory framework for regional asset management, idle asset utilization has not been optimal. This study aims to analyze the implementation of idle asset management policies in Banyuwangi Regency, focusing on the management structure, implementation communication, and implementing agents. This study employed a descriptive qualitative approach. Data were collected through interviews, observations, and documentation studies at the Regional Financial and Asset Management Agency (BPKAD) and related Regional Apparatus Organizations. Informants were selected purposively, and data analysis was conducted interactively, maintaining data validity through triangulation. The results indicate that idle asset management in Banyuwangi Regency is still oriented towards administrative compliance, implementation communication is ineffective and ineffective, and the capacity and initiative of implementing agents are still limited. These conditions result in idle asset utilization not being optimally integrated with regional development. This study emphasizes the need for strengthening the management structure, collaborative policy communication, and increasing the capacity of implementing agents to optimize idle asset management in Banyuwangi Regency.